2012
DOI: 10.1093/humrep/des393
|View full text |Cite
|
Sign up to set email alerts
|

Embryos whose polar bodies contain isolated reciprocal chromosome aneuploidy are almost always euploid

Abstract: STUDY QUESTIONWhen a chromosome aneuploidy is detected in the first polar body and a reciprocal loss or gain of the same chromosome is detected in the second polar body, is the resulting embryo usually aneuploid for that chromosome?SUMMARY ANSWERWhen reciprocal aneuploidy occurs in polar bodies, the resulting embryo is usually normal for that chromosome, indicating that premature separation of sister chromatids (PSSC)—not non-disjunction—likely occurred in meiosis I.WHAT IS KNOWN ALREADYSingle-nucleotide polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…Conversely, nine our of 15 (60%) embryos derived from oocytes with aneuploid polar bodies resulted in a euploid trophectoderm biopsy. This finding is in keeping with previous studies, which have demonstrated that the primary mechanism responsible for aneuploidy in the first polar body is premature sister chromatid separation, allowing the possibility of reciprocal errors in meiosis II (Capalbo et al, 2013;Forman et al, 2013b;Gabriel et al, 2011;Treff et al, 2008). Therefore, it is expected that the accuracy of biopsy of the first polar body stage would not approach the efficiency of trophectoderm biopsy in improving implantation and ongoing pregnancy rates.…”
Section: Discussionsupporting
confidence: 89%
“…Conversely, nine our of 15 (60%) embryos derived from oocytes with aneuploid polar bodies resulted in a euploid trophectoderm biopsy. This finding is in keeping with previous studies, which have demonstrated that the primary mechanism responsible for aneuploidy in the first polar body is premature sister chromatid separation, allowing the possibility of reciprocal errors in meiosis II (Capalbo et al, 2013;Forman et al, 2013b;Gabriel et al, 2011;Treff et al, 2008). Therefore, it is expected that the accuracy of biopsy of the first polar body stage would not approach the efficiency of trophectoderm biopsy in improving implantation and ongoing pregnancy rates.…”
Section: Discussionsupporting
confidence: 89%
“…By using polar-body PGS, only maternally derived meiotic aneuploidies can be diagnosed, whereas mitotic aneuploidies, mosaicism and paternally derived aneuploidies, which are thought to contribute to 3-4% of chromosomal aberrations, are not detected by this method (Hassold and Hunt, 2001). Additionally, possible pitfalls of polar body analysis, such as trisomic rescue or reciprocal aneuploidy, resulting in euploid embryos after aneuploid tested polar bodies, have to be considered when comparing polar body and culture media genetic results (Forman et al, 2013). Up to 20% of embryos shown to be aneuploid by polar-body biopsy have been shown to be euploid after PGS analysis at the blastocyst stage, possibly caused by postzygotic rescue mechanisms (Capalbo et al, 2013;Christopikou et al, 2013;Handyside et al, 2012).…”
Section: Culture Mediummentioning
confidence: 99%
“…Even if no euploid embryos have been obtained at the blastocyst stage, there is no reason to assume that the limitation of PB screening observed here is unique to abnormal oocytes and embryos of poor prognosis AMA patients. Indeed, it has recently been demonstrated in a younger population that when reciprocal aneuploidy occurs from meiosis I premature separation of sister chromatids and compensation in meiosis II, the resulting embryo is usually normal for that chromosome (Forman et al, 2013) and also capable of producing a chromosomally normal child (Scott et al, 2012b). However, we agree that the reproductive potential of these embryos should be further evaluated.…”
mentioning
confidence: 60%